Potential of mucoadhesive chitosan glutamate microparticles as microbicide carriers - antiherpes activity and penetration behavior across the human vaginal epithelium - Emilia Szymańska; Małgorzata Krzyżowska; Krzysztof Cal; Barbara Mikolaszek; Jakub Tomaszewski; Sławomir Wołczyński; Katarzyna Winnicka (Taylor & Francis Group, 2021)
Chitosan glutamate (gCS) spray-dried microparticles appear promising carriers to overcome challenges associated with vaginal microbicide delivery. This study aimed at elucidating the penetration and mucoadhesive behavior of developed gCS multiunit carriers with zidovudine (ZVD) as a model antiretroviral agent in contact with excised human vaginal epithelium followed with an examination of in vitro antiherpes activity in immortal human keratinocytes HaCaT and human vaginal epithelial cells VK2-E6/E7. Both ZVD dispersion and placebo microparticles served as controls. Microparticles displayed feasible (comparable to commercial vaginal product) mucoadhesive and mucoretention characteristics to isolated human vaginal tissue. Ex vivo penetration studies revealed that gCS increased the accumulation of active agent in the vaginal epithelium but surprisingly did not facilitate its penetration across human tissue. Finally, the obtained antiviral results demonstrated the potential of gCS as an antiherpes adjunctive, whose mode of action was related to blocking viral attachment.